Body and character in Luke and Acts : the subversion of physiognomy in early Christianity - Parsons, Mikeal Carl, 1957- (Baker Academic, 2006)
In the ancient world, it was commonly believed that outward appearance provided clues to inner character. The "science" relating physical appearance to moral character is called physiognomy. Mikeal Parsons shows how a number of interesting episodes in Luke and Acts draw upon physiognomy only to subvert it. For example, short physical stature was an indicator of small-mindedness. After his encounter with Jesus, Zacchaeus is still short physically; however, his small-mindedness has been healed, and he repays fourfold those he has defrauded. Thus Luke ultimately denies that any direct line can be drawn between physical appearance and moral character.